2008
DOI: 10.1080/11038120701858804
|View full text |Cite
|
Sign up to set email alerts
|

A review of research with elderly people as respondents reported in occupational therapy journals

Abstract: The aim of this article is to review research presented in occupational therapy journals with the elderly as respondents. With an increasing number of elderly people in society research including the elderly should play a vital role within occupational therapy especially since emphasis on subjective experience is an important factor in the core constructs of occupation. Through a review of six occupational therapy journals, covering the period 2001--2006, it was discovered that 15% of the total number of artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 51 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…In a review of research with elderly people as participants reported in occupational therapy journals (36) it was found that only five articles out of 212 regarding elderly people exclusively concerned persons of 85 years of age and above. These articles investigated the use of assistive devices and their relation to dependence in daily activities among 85-year-olds with age-related macular degeneration (26), the ability to perform ADL, received home adaptations, possession of assistive devices, and perceived health and morale with and without hip fractures was also studied (27), the association between everyday satisfaction and social relations, continuity, self-determination, and use of own resources among 85-year-olds with physical disabilities was investigated (37), the association between interests and functional ability, self-related health, and sociodemographic characteristics of people aged 86 living at home (38), and the personal meaning of ageing and well-being from the perspective of community-dwelling women over 85 years of age (39).…”
Section: Research About the Oldest Oldmentioning
confidence: 98%
“…In a review of research with elderly people as participants reported in occupational therapy journals (36) it was found that only five articles out of 212 regarding elderly people exclusively concerned persons of 85 years of age and above. These articles investigated the use of assistive devices and their relation to dependence in daily activities among 85-year-olds with age-related macular degeneration (26), the ability to perform ADL, received home adaptations, possession of assistive devices, and perceived health and morale with and without hip fractures was also studied (27), the association between everyday satisfaction and social relations, continuity, self-determination, and use of own resources among 85-year-olds with physical disabilities was investigated (37), the association between interests and functional ability, self-related health, and sociodemographic characteristics of people aged 86 living at home (38), and the personal meaning of ageing and well-being from the perspective of community-dwelling women over 85 years of age (39).…”
Section: Research About the Oldest Oldmentioning
confidence: 98%
“…Because health and well-being are influenced by the ordinary familiar things people do in their everyday lives (Clark et al, 1991;Wilcock, 2006); it seems important to enable older adults to keep their daily routines. Yet, little is known about healthy older adults' daily occupations and well-being (Larsson, Haglund, & Hagberg, 2008;Nilsson, Lundgren, & Liliequist, 2012) and the temporal aspects of their everyday lives (Chilvers, Corr, & Singlehurst, 2010;Häggblom-Kronlö f, Hultberg, Eriksson, & Sonn, 2007;McKenna, Broome, & Liddle, 2007). Understanding temporal aspects of daily occupations could contribute to services for older adults' health and well-being Jackson, Carlson, Mandel, Zemke, & Clark, 1998;WHO, 2012).…”
mentioning
confidence: 95%
“…How occupational therapists maintain currency with the latest published research has been described previously [6]. Journals specific to occupational therapy are presumed to represent a primary source for practising occupational therapists' access to research, as these journals are often distributed amongst the members of different occupational therapy associations [7,8]. Criticism has been raised that the research about older people published in occupational therapy journals is of a basic character (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A ten-year-old review of six occupational therapy journals' characteristics concluded that only 15 percent of all published articles included older people as participants. The majority of these studies took a quantitative approach and the topics reported revolved around instrument testing and development [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation